Turkish students’ intercultural challenges and aspirations in U.S. universities: A social media analysis - Oz Cetindere, Esra; Shin, Dong-shin (Journal of International Students, 2025)
In this paper, we present a study of Turkish international students’ experiences in the U.S. by examining data from EksiSozluk, a Turkish social media platform. Drawing on social-emotional learning as a theoretical foundation, we investigated the types of challenges Turkish international students faced in the U.S. and the coping strategies and information they shared with each other. Adopting a thematic analysis, we analyzed the collected data, including 157 entries made by Turkish students about their study abroad experiences in U.S. higher education institutions between 2002 and 2023. The findings suggest that Turkish international students primarily struggle with social and emotional challenges, followed by financial, academic, and cultural issues. The main coping strategies employed by the students were building social relationships through interactions with other Turkish students on social media and seeking cultural knowledge through American pop culture.